Remembering All That and Then Some: Recollection of Autobiographical Memories after a One-Year Delay - Campbell, Jenna (2011)
We previously showed that repeated retrievals of remote autobiographical memories over the course of one month led to an overall increase in reported detail (Nadel, Campbell & Ryan, 2007). The current study examined the retrieval of those same memories one year later in order to determine whether the level of detail remained stable or whether the memories returned to their original state. Participants reported even more details than they had recalled at least one year earlier, including new details that were reported for the first time. This finding was consistent across both multiple and single retrieval conditions suggesting that the critical factor leading to the increase in recall was the passage of time. These findings provide evidence for long-term effects of repeated retrieval on memory content.